Therapeutic Community Treatment Optimization (Findings on Therapeutic Community Treatment in Indonesian Prison) - Hamja; Suratno, Ujang (International Journal of Psychosocial Rehabilitation, 2020)
This article is a brief report on the implementation of the Therapeutic community in Indonesia as an effort to carry out the rehabilitation function in prisons in Indonesia, especially for prisoners of drug abuse. The rehabilitation function with the therapeutic community program is considered capable of providing optimal debriefing for prisoners to face a period of return to the community so that in the end it can reduce the level of drug abuse, recidivism in the same case, and involvement in social life. However, in reality, the success of the therapeutic community program as a manifestation of the rehabilitation function has not yet been properly measured. This report shows various recommendations for optimizing implementation that can be carried out in order to produce accurate measurements related to the successful implementation of the therapeutic community program in Indonesia.